The Transition from Conventional Energy to the Photovoltaic Systems and its Struggle under the Dominant Electricity Regime in Thailand - Krajangthimaporn, Eakanat (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 3 (2020): July-September 2020DO - 10.14456/nujst.2020.23, 2020)
Electricity in Thailand has been heavily dependent on fossil-based fuels, and centrally controlled by the government and associated technocrats. Global issues, such as Cold War, oil and financial crises, along with environmental concerns, have considerably affected the dominant electricity regime of Thailand and driven it towards seeking renewable sources of energy for electricity generation. Photovoltaics, despite its high potential as a sustainable source of electricity, however, remains a supplementary production in the existing electricity regime, not the future electricity transition. In this study, archival data, interviews, and case studies had been analyzed and it was found that the photovoltaic systems in Thailand accounted for only 2.6% of the nation’s total capacity in 2014 while the number is expected to rise to only 8.5% in 2036. Using the Multi-Level Perspective (MLP) concept from the system innovation transition theory, this study explained why photovoltaics cannot be developed into a dominant source of electricity in Thailand. This study also discovered that the development of photovoltaics at the niche level the electricity regime’s existing governance, technology, centralized production and distribution, supply and demand chains of commercial appliances, and culture of the electricity users are not supportive of the photovoltaic systems. Therefore, without significant technological breakthrough and sincere commitment to energy reforms, the photovoltaic systems will continue to struggle and cannot become a major element of the future electricity transition in Thailand. Keywords: Multi-Level Perspective, Landscape change, Thai electricity regime, Photovoltaics